2005
DOI: 10.1103/physrevlett.94.020403
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Self-Trapping of Matter Waves in Periodic Potentials

Abstract: We report the first experimental observation of nonlinear self-trapping of Bose-condensed 87 Rb atoms in a one dimensional waveguide with a superimposed deep periodic potential . The trapping effect is confirmed directly by imaging the atomic spatial distribution. Increasing the nonlinearity we move the system from the diffusive regime, characterized by an expansion of the condensate, to the nonlinearity dominated self-trapping regime, where the initial expansion stops and the width remains finite. The data ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
159
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 254 publications
(180 citation statements)
references
References 12 publications
14
159
1
4
Order By: Relevance
“…With such an analysis, we have confirmed the previous study [6] that the self-trapping observed in optical lattices is closely related to the selftrapping of a BEC in the double-well potential [7,8,10]. From this analysis, we have also explored a possible mechanism of the formation of steep edges.…”
Section: Introductionsupporting
confidence: 74%
See 4 more Smart Citations
“…With such an analysis, we have confirmed the previous study [6] that the self-trapping observed in optical lattices is closely related to the selftrapping of a BEC in the double-well potential [7,8,10]. From this analysis, we have also explored a possible mechanism of the formation of steep edges.…”
Section: Introductionsupporting
confidence: 74%
“…The other frequency ω is so chosen that the initial rms-width of BEC wave packet is 7.6µm as in the experiments [6]. This width corresponds to about 100 wells occupied.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations